An Innovative Three-Step Method for Identifying Exemplars. Issue 1 (1st August 2019) - Etz, Rebecca S.; Gonzalez, Martha M.; Crabtree, Benjamin F.; Reves, Sarah R.; Stange, Kurt C.
Purpose: To improve practices in rapidly changing environments, it is helpful to learn from relevant innovators. This article describes a well-defined and adaptable method for discovering innovative cases that inform best practices or positive/negative deviant research. Methods: As part of a national study of innovation in primary care settings, we developed a three-step method for identifying exemplar practices and applied that method to finding a sample of relevant innovators for in-depth case studies from which to draw transportable lessons about improving primary care practice. Results: Relevant, information-rich cases are uncovered using cycles of identification, sampling, and assessment. This cycle is repeated at each step of the defined three-step method. Step 1, a scan of the published literature, assesses both the state-of-the-art and the baseline characteristics of relevant cases; Step 2, a scan of practice settings, draws upon the expert knowledge of key informants to identify additional potentially relevant cases; and Step 3, sample refinement, evaluates potential cases for eligibility, purposeful diversity, and information-rich expressions of defined key domains. Using this three-step method, we identified a national cohort of primary care practice innovators. We found the method to be feasible, practical, and highly successful at identifying information-rich practices from which to draw transportable lessons about practice innovation. Conclusions: The three-step method outlines an effective sampling strategy for identifying innovation exemplars and information-rich cases that exceed measures of central tendency. By leveraging the collective knowledge of innovators, this method can support dynamic research and foster rapid cycle learning.